2011
DOI: 10.1074/jbc.m111.270413
|View full text |Cite
|
Sign up to set email alerts
|

Fascin Protein Is Critical for Transforming Growth Factor β Protein-induced Invasion and Filopodia Formation in Spindle-shaped Tumor Cells

Abstract: Background: Fascin is a pro-metastasis actin-bundling protein overexpressed in metastatic tumors. Results: TGF␤ induced fascin expression in spindle tumor cells through Smads. Conclusion: Fascin is a TGF␤ target gene essential for the pro-invasion activity of TGF␤. Significance: Our data shed new light on how TGF␤ dysregulates actin cytoskeleton to promote tumor metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
52
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 43 publications
2
52
1
Order By: Relevance
“…Previous studies suggested that many factors regulated fascin expression in cancer cells, such as miR-145, EGF receptor, and TGF-b (36)(37)(38)(39). Our data revealed that hypoxia in the PDAC microenvironment upregulate fascin expression through HIF-1.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies suggested that many factors regulated fascin expression in cancer cells, such as miR-145, EGF receptor, and TGF-b (36)(37)(38)(39). Our data revealed that hypoxia in the PDAC microenvironment upregulate fascin expression through HIF-1.…”
Section: Discussionsupporting
confidence: 56%
“…Our data further suggested that fascin overexpression increased MMP-2 expression through PKC-ERK signaling, which may at least partially account for the elevated invasiveness in fascin-overexpressing PDAC cells. It is also worth noting that fascin has been implicated in invadopodium formation in melanoma and breast cancer (39)(40)(41). It remains to be determined whether fascin-mediated invadopodia formation is involved in PDAC invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…We chose this antibody because many studies have utilized anti‐fascin‐1 antibody with a clone of 55k‐2 from such companies as Santa Cruz Biotechnology 18, Dako 12, and Cell Marque 13. Therefore, we choose this type of fascin‐1 antibody from one of those companies.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of fascin has been reported in almost all the carcinomas (2,14,26,27), and fascin overexpression uniformly correlates with aggressive clinical course, metastatic progression, and poor prognosis (14, 28 -33). The transcriptional regulation of fascin in cancer has been extensively studied, with inflammatory cytokines, hypoxia, epithelial to mesenchymal transcription factors, and Wnt/␤-catenin pathways, among others, being implicated in the up-regulation of fascin levels in various cancers (33)(34)(35)(36)(37)(38). In contrast, little is known about the post-translational regulation of fascin other than the Ser 39 phosphorylation by PKC.…”
Section: Discussionmentioning
confidence: 99%